2014
DOI: 10.1007/s00277-014-2006-3
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary gene mutations in Korean patients with isolated erythrocytosis

Abstract: Most cases of erythrocytosis occur secondary to chronic tissue hypoxia or as a clonal disease such as polycythemia vera with somatic mutations in the Janus kinase 2 (JAK2) gene. Rarely, erythrocytosis is caused by hereditary gene mutations. This study investigated hereditary gene mutations in 38 unrelated Korean patients with isolated erythrocytosis without (1) JAK2 mutation and (2) secondary causes of erythrocytosis other than smoking history. Direct sequencing analyses were performed on six genes associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…EGLN1 p.L279P affects a conserved residue, previously reported as altered (p.L279Tfs43, a frameshift variant) in a patient with erythrocytosis. 20 Structurally, this 12 47 …”
Section: Novel Genes and Variants Identified By The Erythrocytosis Gementioning
confidence: 99%
“…EGLN1 p.L279P affects a conserved residue, previously reported as altered (p.L279Tfs43, a frameshift variant) in a patient with erythrocytosis. 20 Structurally, this 12 47 …”
Section: Novel Genes and Variants Identified By The Erythrocytosis Gementioning
confidence: 99%
“…For example, Bento, et al8 reported that only 25 of 70 patients (36%) had a known causative gene defect. Similarly, only 13.2 % of Korean patients with erythrocytosis had a known causative gene mutation 6. Therefore, further studies are needed to identify the new genetic cause of erythrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital (familial) erythrocytosis was suspected. We performed alpha 1-globin gene ( HBA1 )/alpha 2-globin gene ( HBA2 ), beta-globin gene ( HBB ), and Von Hippel Lindau ( VHL ) gene mutation analysis according to a previous study 6. All coding sequences and flanking intronic regions of HBA1/HBA2 , HBB , and VHL were analyzed.…”
Section: Case Reportmentioning
confidence: 99%
“…Lastly, it is important to rule out a hereditary background [ 23 ]. Recent data in Korea revealed a significant proportion (13.2%) of patients with JAK2 -negative idiopathic isolated erythrocytosis had germline mutations [ 24 ].…”
Section: Molecular Genetics Of Mpnsmentioning
confidence: 99%
“…The NHI program covers the entire Korean population as a compulsory social insurance system. Age-standardized incidence rates are estimated by calculating weighted averages of crude age-specific rates, using the mid-year estimated population of Korea in the year 2000 as the standard population, and calculated using the world standard population as the reference population [ 24 ].…”
Section: Epidemiologymentioning
confidence: 99%